Progress towards ending hunger and malnutrition: A cross-country cluster analysis - Food and Agricultural Organization of the United Nations; International Food Policy Research Institute; Laborde Debucquet, David; Mamun, Abdullah; Vos, Rob (Food and Agricultural Organization of the United Nations, 2020)
This report provides a quantitative assessment of progress made towards the sustainable development goal of ending hunger and all forms of malnutrition since 1990. Using a cluster analysis, it categorizes country performance along three dimensions: (1) food security and nutrition outcomes; (2) structural drivers of food security and nutrition; and (3) past and present policy interventions in support of food security and nutrition. Key findings show that much progress has been made towards the goal of ending hunger. Yet, many countries continue to face moderate to high degrees of undernourishment, especially where economies made least progress in transitioning towards high-productivity, modern agriculture and non-farm economic development and where policy stances have been weak in promoting agricultural development, reducing gender inequalities, and improving infrastructure and basic social services. The decline in undernourishment has come with a rise in the prevalence in overweight and obesity. The spread of this form of malnutrition has come with dietary shifts towards the consumption of more animalsourced and processed foods that have accompanied urbanization and income growth. By 2015, the vast majority of countries faced moderate to high prevalence of adult overweight, and this form of malnutrition is also on the rise in countries with still significant rates of child undernourishment. No country in the world is showing declines in the rate of adult overweight.